2020
DOI: 10.3390/ma13102209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti Content on the Microstructure and Corrosion Resistance of CoCrFeNiTix High Entropy Alloys Prepared by Laser Cladding

Abstract: In this paper, CoCrFeNiTix high entropy alloy (HEA) coatings were prepared on the surface of Q235 steel by laser cladding. The microstructure, microhardness, and corrosion resistance of the coatings were studied. The mechanism of their corrosion resistance was elucidated experimentally and by first-principles calculations. The results show that CoCrFeNiTi0.1 adopts a face-centered cubic (FCC) phase, CoCrFeNiTi0.3 exhibits an FCC phase and a tetragonal FeCr phase, and CoCrFeNiTi0.5 adopts an FCC phase, a tetrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…In the majority of cases, multicomponent alloys are synthesized by crystallization from the melt (arc or induction melting in vacuum or argon [5][6][7][13][14][15][16][17][18][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], plasma spark sintering [19], electric current assisted sintering [20,21], laser or plasma cladding deposition of coatings [44][45][46][47][48][49][50][51][52][53][54][55], additive manufacturing by the laser-powder bed fusion [56,57] or laser-metal deposition [58], self-propagating high-temperature synthesis (SHS) [59], and by brazing within the brazing joints [60,61]). Figure 1 shows a schematic phase diagram for the simplest case when there are on...…”
Section: Grain Boundary Wetting By the Liquid Phasementioning
confidence: 99%
“…In the majority of cases, multicomponent alloys are synthesized by crystallization from the melt (arc or induction melting in vacuum or argon [5][6][7][13][14][15][16][17][18][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], plasma spark sintering [19], electric current assisted sintering [20,21], laser or plasma cladding deposition of coatings [44][45][46][47][48][49][50][51][52][53][54][55], additive manufacturing by the laser-powder bed fusion [56,57] or laser-metal deposition [58], self-propagating high-temperature synthesis (SHS) [59], and by brazing within the brazing joints [60,61]). Figure 1 shows a schematic phase diagram for the simplest case when there are on...…”
Section: Grain Boundary Wetting By the Liquid Phasementioning
confidence: 99%
“…In the majority of cases, HEAs are manufactured by crystallization from the melt after arc or induction melting [5][6][7][8][9][10][11][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], electric current assisted sintering [35,36], plasma spark sintering [37], additive manufacturing by the laser powder bed fusion [38,39] or laser metal deposition [40], laser or plasma cladding deposition of coatings [41][42][43][44][45][46][47][48][49][50][51][52], selfpropagating high-temperature synthesis (SHS) [53], or even by brazing of dissimilar materials within the brazing joints [54,55]). In some cases, the liquid phase is not present during the synthesis of HEAs such as in the case of sputter deposition of coatings…”
Section: Grain Boundary Wetting By the Second Solid Phasementioning
confidence: 99%
“…In order to study the effect of the Ti element on the wear resistance of the coating prepared by laser cladding, Wang X. et al (2020) studied CoCrFeNiTix HEA coatings with different Ti content and found that the hardness and corrosion resistance of the coatings increased with the addition of Ti content. Furthermore, the main corrosion mechanism of CoCrFeNiTix high entropy coatings in 3.5wt% NaCl solution is pitting corrosion.…”
Section: Fabrication Methods Of Titanium Based Heasmentioning
confidence: 99%